MiR-23b-3p acts as a counter-response against skeletal muscle atrophy. Issue 3 (March 2020) - Okamura, Takuro; Hashimoto, Yoshitaka; Osaka, Takafumi; Senmaru, Takafumi; Fukuda, Takuya; Hamaguchi, Masahide; Fukui, Michiaki
Abstract : To investigate the role of microRNA (miRNA) in muscle atrophy, we performed microarray analysis of miRNA expression in skeletal muscles of Sham, orchiectomized (ORX) mice, and ORX mice treated with androgen and identified that the expression of miR-23b-3p in ORX mice was significantly higher than that in Sham mice ( P  = 0.007); however, miR-23b-3p expression in ORX mice treated with androgen was lower ( P  = 0.001). We also investigated the mechanism by which overexpression or knockdown of miR-23b-3p influences the expression of myosin heavy chain, muscle protein synthesis, ATP activity, and glucose uptake in C2C12 myotube cells. Moreover, we examined the serum miR-23b-3p levels among male subjects with type 2 diabetes and whether the serum miR-23b-3p levels could be a biomarker for muscle atrophy. The overexpression of miR-23b-3p in C2C12 myotube cells significantly upregulated the expression of myosin heavy chain, protein synthesis, ATP activity, and glucose uptake. Reporter assays raised a possible direct post-transcriptional regulation involving miR-23b-3p and the 3′-UTR of PTEN mRNA. Among subjects with type 2 diabetes, serum miR-23b-3p levels in the subjects with decreased muscle mass were significantly higher compared to the levels in the subjects without. Our results indicate that miR-23b-3p downregulates the expression of PTEN in myotube cells and induces the growth of myosin heavy chain. In addition, the serum level of miR-23b-3p can be used as a diagnostic marker for muscle atrophy.